The mediation system of China from an interdisciplinary perspective / Hao Xiong, Fudan University, Shanghai. - Xiong, Hao (Cambridge University Press, 2025)
Delivering a much-needed in-depth, interdisciplinary exploration of mediation practices in China, this study removes the common misconception that mediation is merely a mechanical application of norms. It provides a comprehensive understanding of China's mediation practices by blending cultural, social, and legal analyses with detailed case descriptions from fieldwork. Readers will gain insights into the interactive dynamics between legal norms and the social environment in grassroots China. This book helps readers understand mediation and Chinese law within their broader cultural, social, and political contexts, offering insights beyond the purely legal dimension. The book is an invaluable resource for scholars, students, and practitioners in the fields of Chinese law, dispute resolution, and socio-legal studies. It offers a unique perspective that contextualizes mediation within the socio-political landscape, providing readers with a richer, more nuanced understanding of Chinese legal culture.